Chatbot sebagai Asisten Customer Service dan Public Relations di Indonesia: Studi Difusi Inovasi Teknologi - Nunung Nasikhah; Gustaf Wijaya; Titik Puji Rahayu (Jurnal Sosioteknologi, 2022)
Chatbot technology is one of the tools to improve service. In chatbots, communicationis no longer between humans and humans, but between humans and machines or robots,despite it still use human language. In Indonesia, the literature on chatbots is morefocused on the technological aspect, while the communication aspect is still inadequate.This research is a diffusion of innovations study to explain the dissemination ofchatbots’ adoption in Indonesia. Data through interviews with five sources withdifferent backgrounds. Researchers target government agencies as users of chatbotapplications to serve the public, also micro businesses that use automation, and a chatbotprovider as an active party in communicating chatbot technology. Researchers alsoexplore the experiences gained by end-user chatbots. The findings show that the mainreasons for adopting chatbots in Indonesia are the swiftness of service, the efficiencyof human resources, and the unlimited working hours. This leads to chatbots easingthe information process, both customer services, and public relations. The mass mediacommunication channel is used to introduce chatbot services to the public. While theinterpersonal communication channel is used to transfer knowledge from the developerto the administrator.